Phenol photocatalytic degradation over mesoporous TUD-1-supported chromium oxide-doped titania photocatalyst - Ooi, Y. K. (Science Press, 2016)
Mesoporous Technische Universiteit Delft (TUD-1)-supported chromium oxide-doped titania (Cr-TiO2) was developed as a promising photocatalyst for phenol photodegradation under visible light irradiation. Low-angle X-ray diffraction and Fourier transform infrared spectroscopy results confirmed the amorphous and mesoporous silicate framework of TUD-1 in TUD-1-supported Cr-TiO2. The mesostructure of TUD-1 was further verified via N2 adsorption-desorption analysis, which showed a type-IV isotherm with a narrow average pore size distribution of 3.9 nm and high surface area of > 490 m2/g. Transmission electron microscopy analysis results indicated that TUD-1-supported Cr-TiO2 contained nanoparticles and porous channels. An increase in band gap energy was observed after loading Cr-TiO2 into TUD-1. Compared with that of unsupported Cr-TiO2, TUD-1-supported Cr-TiO2 showed higher photocatalytic activity for phenol degradation under visible light irradiation. The TUD-1 supported Cr-TiO2 photocatalyst with a Si/Ti molar ratio of 30 exhibited the highest photodegradation of phenol (82%) of the prepared samples. The photodegradation of phenol by the supported catalyst followed the Langmuir adsorption isotherm with first-order kinetics.